OPTIMIZATION OF POLYHYDROXALKANOATE ACCUMULATION BY KLEBSIELLA SP. NCCP-138 ISOLATED FROM OIL CONTAMINATED SOIL - SUSHMA SHENOY; JOYLINE MASCARENHAS; ARUNA. K (International Journal of Pharma and Bio Sciences, 2012)
Hydrocarbon polymers of microbial origins, such as polyhydroxyalkanoate (PHA) are considered to be major components of biodegradable plastics. PHA producing bacterium was isolated from oil contaminated soil and identified as Klebsiella species NCCP- 138 on morphological, cultural, biochemical tests and 16S rRNA sequence analysis. Maximum PHA accumulation of 1.89g/l was achieved with an inoculum size of 10% (0.8 OD530nm) and the isolate was grown in PHA production medium containing 2.5% Mannitol, 0.5% Yeast Extract, 1% Peptone and pH 7.5 at 35°C under static condition for 72 hr. Further characterization of PHA was carried out using Fourier transform infrared spectroscopy (FT-IR).